On Cluster Points of Sequences via Fuzzy Topology - Jyothis K Mohan; Sheeja T K; Sunny Kuriakose A (Sahand Communications in Mathematical Analysis)
The notion of fuzzy convergence, a prominent tool in fuzzy analysis, has wide applications in fuzzy inference. The present paper examines the distinctive features of the cluster points of fuzzy sequences in various fuzzy topological spaces. A characterization of the fuzzy indiscrete space regarding the cluster points is obtained. Moreover, a detailed study of the cluster points of fuzzy sequences in fuzzy indiscrete, fuzzy discrete, fuzzy co-countable and fuzzy co-finite spaces is presented and characterizations of the cluster points in each space are established. Furthermore, the concepts of maximal cluster points, $c$-sets, $c_m$-sets and fuzzy $c$-sets of fuzzy sequences are proposed and their properties are investigated.